Implications of COVID-19 on Progress in the UN Conventions on Biodiversity and Climate Change - Ortiz, Andrea Monica D (Archīum Ateneo, 2021)
2020 was to be a landmark year for setting targets to stop biodiversity loss and prevent dangerous climate change. However, COVID-19 has caused delays to the 15th Conference of the Parties (COP) of the UN Convention on Biological Diversity and the 26th COP of the UN Framework Convention on Climate Change. Negotiations on the Global Biodiversity Framework and the second submission of Nationally Determined Contributions under the Paris Agreement were due to take place at these COPs. There is uncertainty as to how the COVID-19 disruption will affect the negotiations, whether parties will pursue more ambitious actions or take a weaker stance on issues. Our policy analysis shows there are broad opportunities for climate and biodiversity frameworks to better respond to COVID-19, by viewing future pandemics, biodiversity loss, and climate change as interconnected problems. Importantly, there needs to be greater focus on agriculture and food systems in discussions, establishing safeguards for carbon markets, and implementing nature-based solutions in meeting the Paris Agreement goals. We can no longer delay action to address the biodiversity and climate emergencies, and accelerating sustainable recovery plans through virtual spaces may help keep discussions and momentum before the resumption of in-person negotiations.